Managing complexity in the operating room: a group interview study - Camilla Göras; Ulrica Nilsson; Mirjam Ekstedt; Maria Unbeck; Anna Ehrenberg (BMC Health Services Research, 2020)
Abstract Background Clinical work in the operating room (OR) is considered challenging as it is complex, dynamic, and often time- and resource-constrained. Important characteristics for successful management of complexity include adaptations and adaptive coordination when managing expected and unexpected events. However, there is a lack of explorative research addressing what makes things go well and how OR staff describe they do when responding to challenges and compensating for constraints. The aim of this study was therefore to explore how complexity is managed as expressed by operating room nurses, registered nurse anesthetists, and surgeons, and how these professionals adapt to create safe care in the OR. Method Data for this qualitative explorative study were collected via group interviews with three professional groups of the OR-team, including operating room nurses, registered nurse anesthetists and operating and assisting surgeons in four group interview sessions, one for each profession except for ORNs for which two separate interviews were performed. The audio-taped transcripts were transcribed verbatim and analyzed by inductive qualitative content analysis. Results The findings revealed three generic categories covering ways of creating safe care in the OR: preconditions and resources, planning and preparing for the expected and unexpected, and adapting to the unexpected. In each generic category, one sub-category emerged that was common to all three professions: coordinating and reaffirming information, creating a plan for the patient and undergoing mental preparation, and prioritizing and solving upcoming problems, respectively. Conclusion Creating safe care in the OR should be understood as a process of planning and preparing in order to manage challenging and complex work processes. OR staff need preconditions and resources such as having experience and coordinating and reaffirming information, to make sense of different situations. This requires a mental model, which is created through planning and preparing in different ways. Some situations are repetitive and easier to plan for but planning for the unexpected requires anticipation from experience. The main results strengthen that abilities described in the theory of resilience are used by OR staff as a strategy to manage complexity in the OR.